Wydolnosc beztlenowa miesni konczyn dolnych mlodocianych zapasnikow - Gierczuk, D.; Dlugolecka, B. (Polish Journal of Sport and Tourism, 2009)
Changes in the way of wrestling enforce change of its structure, and thus the nature of the competitor`s physical effort. This problem is still present and requires a deeper analysis of wrestlers` physical fitness. The aim of this study was to determine the change in the level of selected indicators of lower limb anaerobic capacity in the students of the Sporting Championship School involved in the classical style wrestling. The tests were carried out three times at intervals of one year and on the same group of competitors at the beginning of the second preparatory period for 2006, 2007 and 2008. Assessment of the anaerobic capacity of the lower limbs (in alactic anaerobic energy output) was performed based on the Wingate test on a Monark 874E cycloergometer, determining the following parameters: maximal power output (W·kg-1); total work output performed by the competitor during the test (J·kg-1) as well as a time to attain maximal power output and a time to sustain maximal power output (s). It was found that the level of the assessed parameters of lower limbs anaerobic capacity of classical style wrestlers increased along with their age and training experience. The greatest improvement in wrestlers aged 16 to 18 years was noted in maximal power output and the time to sustain maximal power output. The high indicators of variability (V%) in the time to attain and sustain of maximal power output, show that there are large reserves of anaerobic capacity of the lower limbs of the tested wrestlers, regardless of the level of their sporting advancement.